Lactococcus lactis D4 Decreases NF-κB and α-SMA in Rat Models of Obstructive Jaundice - Avit Suchitra; Alvarino Alvarino; Eryati Darwin; Harnavi Harun; Muhammad Iqbal Rivai; Ade Sukma (Indonesian Biomedical Journal)
BACKGROUND: Obstructive jaundice, often due to choledocholithiasis or malignancies, leads to immune suppression, intestinal damage, and bacterial translocation, worsening outcomes. Some inflammatory mediators like nuclear factor kappa B (NF-κB), alpha-smooth muscle actin (α-SMA), and interleukin-6 (IL-6) are important in this process. Current treatments remain inadequate, highlighting the need for novel approaches. Probiotics, such as Lactococcus lactis D4 (LLD4), may help reduce inflammation and bacterial translocation, thus offering a potential therapeutic option. This study was conducted to evaluate the effects of LLD4 on NF-κB, α-SMA, and IL-6 in obstructive jaundice rat models.